Foreign direct investment, institutional quality and economic growth in Kenya - Meah, Daudi O.; Onono, Perez A.; Ocharo, Kennedy N. (My University, 2016)
The study was done to investigate the effect of FDI on economic growth in Kenya, to determine the influence of institutional quality on the effect of FDI on economic growth, and to determine the effects of structural breaks on economic growth in Kenya. This was based on the failure of the reviewed studies to capture the role of institutional quality in this effect. Markets that are likely to persist in low-quality-institution jurisdictions are those in which exchange is simultaneous and self-reinforcing. Such markets are common either because many of the exchanges simply meet the conditions for self-reinforcement or just because they are so lucrative that the absence of selfreinforcement makes even risky exchanges worthwhile. However, many transactions require a third party for their reinforcement. These are non-simultaneous transactions whereby the quid is needed at one time or place and the pro at another. Data used in the study were obtained from published sources for the period 1975 to 2013 and they were subjected to statistical analysis. To answer objective one, two, and three the study used ordinary least square estimation and the findings were that FDI affects economic growth positively and institutional quality has a growthenhancing effect on FDI.
Keywords: Foreign Direct Investments; Institutional Quality; Economic Growth; Kenya